الفكر الإصلاحي في الجزائر - باحدي, موسى; فرجانى, التجاني; قطرون, محمد (جامعة الوادي - University of Eloued, 2023)
لقد شملت دراستنا هذه جذور الفكر الإصلاحي في الجزائر ما بين 1933-1939 هذه الفترة برزت فيها الجمعية العلماء المسلمين الجزائريين والتي كان لرواها الأثر البليغ في نشاطها وتأثيرها على المجتمع الجزائري ابان الاستعمار الفرنسي . لقد مثلت الجرائد وسيلة وسائلها وأداة مهمة في نشر الوعي والإصلاح بين أوساط الشعب الجزائري لتحريره الجهل والخنوع حيث تناولنا جانبا مهما منها في شتى المجالات السياسية والعلمية والاجتماعية وكذلك الثقافية.Our study included the roots of reformist thought in Algeria between 1933-1939. During this period, the Association of Algerian Muslim Scholars emerged, whose narrators had an eloquent impact on its activity and impact on Algerian society during the French colonial era. The poems represented a means and an important tool in spreading awareness and reform among the Algerian people to liberate them from ignorance and subservience, as we dealt with an important aspect of them in various political, scientific, social and cultural fields.
من خلال جرائد جمعية العلماء الدسلمين الجزائريين
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: الفكر الاصلاحي - جمعية العلماء المسلمين - الصحافة الاصلاحية - جرائد الجمعية; Reformist Thought - Association of Muslim Scholars - Reformist Press - Association Newspapers